EU Citizenship and Withdrawals from the Union: How Inevitable Is the Radical Downgrading of Rights? - Dimitry Kochenov (London School of Economics and Political Science (LSE), European Institute, 2016)
What are the likely consequences of Brexit for the status and rights of British citizenship? Can the fact that every British national is an EU citizen mitigate the possible negative consequences of the UK's withdrawal from the EU on the plane of rights enjoyed by the citizens of the UK? These questions are not purely hypothetical, as the referendum on June 23 can potentially mark one of the most radical losses in the value of a particular nationality in recent history. This paper reviews the possible impact that the law and practice of EU citizenship can have on the conduct of Brexit negotiations and surveys the possible strategies the UK government could adopt in extending at least some EU-level rights to UK citizens post-Brexit. The high cost of such rights at the negotiating table is discussed against the general backdrop of the legal-historical analysis of the tradition of flexibility in citizenship and territorial governance which clearly emerges in EU law once the post-colonial context is considered in full. A particular emphasis is put on the possibility of negotiating post-Brexit bilateral free-movement arrangements with select Member States: a deeply problematic practice from the point of view of non-discrimination and the basic idea of European unity. Aiming to address the core issues of the role of EU citizenship in the context of withdrawals from the Union the conclusions of the paper, pointing to a quasi-inevitable overwhelming downgrade in citizenship rights for the withdrawing state, are applicable to any withdrawal context, not limited to the UK per se.
Keywords: 330; Brexit; EU citizenship; non-discrimination; flexibility; free movement